Use of Kb Implant In Palangga Gowa Health Center - Hanifah, Astin Nur; Qamarya, Nurul; Wahyuni, Sri; Hilmiah, Hilmiah; Rahmawati, Agustini Liviana Dwi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
The implant is a contraceptive device containing levonorgetrel which is wrapped in a silastic silicone capsule and placed under the skin. Types of Case Study Research. The aim of this research is to carry out midwifery care with Implant Installation Acceptors at the Pallangga Community Health Center, Gowa Regency using a Midwifery Care approach according to the midwife's competence and authority. This research method uses Varney's seven-step method which includes identification of basic data, formulating a diagnosis/actual problem, formulating a diagnosis/problem, immediate action/collaboration, implementation intervention, and evaluation of midwifery care for KB implant acceptors and documentation. The result is that the KB implant inhibits the release of eggs and ovaries by releasing progesterone slowly in the mother's body. Progesterone thickens the mucus and makes it difficult for the uterus to accept a fertilized egg. All care is documented with the results of midwifery care in the form of SOAP.